Optimizing the endoscopic diagnosis of mediastinal lymphadenopathy: a glimpse on cryobiopsy - Mondoni, Michele; Sotgiu, Giovanni (BMC pulmonary medicine, 2022)
Etiological diagnosis of mediastinal lymphadenopathy represents a daily challenge. Endosonography (transesophageal and transbronchial ultrasound-guided needle aspiration) is the recommended technique in the first diagnostic work-up and in the mediastinal staging of lung cancer. Despite a good sensitivity, limited amount of collected tissue may hamper molecular assessment in advanced lung cancer and in the diagnosis of lymphoproliferative disorders, fibrotic sarcoidosis, and mycobacterial lymphadenitis. Cryobiopsy, a bronchoscopic technique based on cooling, crystallization, and subsequent collection of tissue, has been successfully employed in the diagnosis of interstitial lung diseases. Cryoprobes provide larger amount of tissue than conventional bronchoscopic sampling tools and might potentially prevent the need for invasive surgical procedures. New applications of the technique (e.g., bronchoscopic diagnosis of peripheral pulmonary lesions and mediastinal lymph nodes) have been recently described in few reports. In a recent issue of the Journal, Genova et al. described five patients who underwent endobronchial ultrasound transbronchial needle aspiration (EBUS-TBNA) followed by ultrasound-guided transbronchial cryobiopsy of mediastinal lymphadenopathy for a suspected malignancy. The authors discussed about the potential added value of mediastinal cryobiopsy on a correct histopathological and molecular assessment in patients with malignancies. EBUS-cryobiopsy could be a promising technique in the diagnostic pathway of mediastinal lymphadenitis. However, cryobiopsy is now available only in few selected centres. The learning curve of the technique adapted to mediastinal ultrasound-guided sampling, the optimal sampling strategy, its true diagnostic accuracy in patients with malignant and benign diseases, as well as its safety, are still largely unclear. Mediastinal cryobiopsy could be complementary rather than alternative to conventional endosonography. Rapid on-site evaluation of EBUS-TBNA could guide subsequent sampling with cryoprobes in case of poor collection of biological material or in case of suspected lymphoproliferative disorders. Further studies should investigate its diagnostic yield, in comparison or in combination with conventional endosonography, in large cohorts of patients with malignant or benign mediastinal lymphadenopthies.